Product Creativity as an Identity Issue: Through the Eyes of New Product Development Team Members - Park, Jin Suk; Suzuki, Satoko (Frontiers in Psychology, 2021)
In this paper, we introduce a concept of product identification that denotes the overlap between identities of a new product and its developer. As the creativity is the most important identity dimension in the new product, we draw on two dimensions of creativity: novelty and meaningfulness. According to the argument that novelty represents exploration, whereas meaningfulness represents exploitation, we hypothesize that product novelty is associated with an explorative behavior of new product team members, while product meaningfulness is associated with exploitative behavior. More importantly, product identification is proposed as the mechanism that explains the amplification effect of product identity on the team members. Based on survey data collected from 200 Japanese new product development (NPD) team members, we conduct a statistical analysis to test the hypotheses. The findings demonstrate the alignment between a new product’s identity and NPD members’ behaviors, which is amplified by product identification but not by organizational identification.